2003
DOI: 10.1021/bi030055o
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic and Mutational Analysis of the Blue-Light Photoreceptor AppA:  A Novel Photocycle Involving Flavin Stacking with an Aromatic Amino Acid

Abstract: The flavoprotein AppA is a blue-light photoreceptor that functions as an antirepressor of photosynthesis gene expression in the purple bacterium Rhodobacter sphaeroides. Heterologous expression studies show that FAD binds to a 156 amino acid N-terminal domain of AppA and that this domain is itself photoactive. A pulse of white light causes FAD absorption to be red shifted in a biphasic process with a fast phase occurring in <1 micros and a slow phase occurring at approximately 5 ms. The absorbance shift was sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

33
237
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 158 publications
(272 citation statements)
references
References 39 publications
33
237
2
Order By: Relevance
“…This mechanism also can explain why the photoactivated state is so stable and lives from seconds in Slr1694 to a half-hour in AppA. In support of this hypothesis, mutation of the conserved Tyr or the conserved Gln results in a complete loss of photocycling activity (12,15,16,28,29). With the R. sphaeroides BlrB structure at hand, Jung et al (13) presented an alternative that would imply a light-induced PT from Arg-32 to the O2 of the flavin from FAD*.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…This mechanism also can explain why the photoactivated state is so stable and lives from seconds in Slr1694 to a half-hour in AppA. In support of this hypothesis, mutation of the conserved Tyr or the conserved Gln results in a complete loss of photocycling activity (12,15,16,28,29). With the R. sphaeroides BlrB structure at hand, Jung et al (13) presented an alternative that would imply a light-induced PT from Arg-32 to the O2 of the flavin from FAD*.…”
Section: Discussionmentioning
confidence: 78%
“…Previous studies on flavo-enzymes have revealed that rapid light-driven ET may occur from aromatic residues to flavin (25,26). Tyr-8 (Tyr-21 in AppA) is a good candidate because it is the closest aromatic residue to the flavin and has been shown to be critical for photocycling activity in BLUF domains (12,15,16). The redox properties of flavin and Tyr gives a favorable driving force for the ET reaction: the midpoint potential for flavin͞flavin •Ϫ is approximately Ϫ0.8 V and for Tyr͞Tyr •ϩ is Ϸ0.93 V (25,27), providing a driving force for ET of ⌬G ϭ Ϫ0.62 eV given that the energy of the 0-0 transition of S 0 3 S 1 is Ϸ 2.35 eV (1 eV ϭ 1.602 ϫ 10 Ϫ19 J) (27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main interfacing residues occur along a loop (Ile-83-Val-90) located between the fourth and fifth ␤-strands, the start of the fifth ␤-strand (Trp-91-Met-93), and two C-terminal helices. At the joint between this loop and the fifth ␤-strand are highly conserved residues Trp-91 and Met-93 that undergo major conformational changes in response to light as suggested by crystallographic analysis of several BLUF proteins, FTIR, and static fluorescence studies (10,11,13,24) (Fig. 5B).…”
Section: Discussionmentioning
confidence: 92%
“…Recently, details of the AppA photo-excitation process emerged (16,17). Whereas the fully oxidized AppA at high oxygen tension and the fully reduced AppA at low oxygen tension mediate the redox signal independently of light, at intermediate oxygen concentrations light determines whether AppA releases the repressing effect of PpsR (7).…”
mentioning
confidence: 99%